2020
DOI: 10.1111/1759-7714.13313
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation for the diagnosis and management of immune checkpoint inhibitor related infections

Abstract: Immune checkpoint inhibitors (ICIs) have been widely used in the management of malignant tumors. Programmed death 1 (PD‐1)/PD‐1 ligand (PD‐L1) inhibitors have been introduced to treat non‐small cell lung cancer (NSCLC) in recent years. Currently, PD‐1/PD‐L1 inhibitors are considered to have minor side effects and do not independently increase the risk of infection. However, they may cause immune‐related adverse events (irAEs) that require immunosuppressive therapy with corticosteroids and/or immunosuppressants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
(83 reference statements)
0
7
0
1
Order By: Relevance
“…Several studies showed that mice with PD1 deletion appear to have significantly increased proinflammatory cytokines, resulting in excessive inflammation, and therefore uncontrolled bacterial growth [9]. A boost of T helper cell TH1 function is another possible explanation and can be compared to the immune reconstitution inflammatory syndrome (IRIS) in HIV patients [10]. The same reasoning can be applied to T. gondii infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that mice with PD1 deletion appear to have significantly increased proinflammatory cytokines, resulting in excessive inflammation, and therefore uncontrolled bacterial growth [9]. A boost of T helper cell TH1 function is another possible explanation and can be compared to the immune reconstitution inflammatory syndrome (IRIS) in HIV patients [10]. The same reasoning can be applied to T. gondii infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies must be conducted because of divergent results. Indeed, some studies have noted that enhancement of the T cell by PD-1/PD-L1 blockage can lead to pathogen elimination [10]. Indeed, chronic infection induces CD8+ T cell exhaustion via the PD1-PDL-1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…50 Moreover, reactivation of latent infections, such as tuberculosis, has also been described. 51 In addition, in the time of coronavirus disease 2019 pandemic, severe acute respiratory syndrome coronavirus 2 infection should be considered in case of new-onset pulmonary changes detected 2. Rhinovirus bronchiolitis during maintenance therapy with nivolumab in a 64-year-old woman with metastatic melanoma.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Opportunistic infection represents the most important complication of irAEs and is often owing to the steroid, immunosuppressive or immunomodulatory, treatment required to control the disease 18,51 (Fig. 10).…”
Section: Complicationsmentioning
confidence: 99%
“…However, when irAEs set in that require additional immunosuppressive therapy with high-dose corticosteroid and/or other biologic or non-biologic immunosuppressants, the risk of invasive fungal disease is significantly increased. Some authors have recommended routine pretreatment screening for latent/chronic infections such as latent tuberculosis and viral hepatitis, 93 but there is a lack of evidence support, and it is unclear whether the screening strategy should be generalized to involve opportunistic fungal infection, e.g., histoplasmosis. Apart from the established guideline on PJP prophylaxis in patients treated with prolonged high-dose corticosteroid, the role of antibacterial, antifungal, and/or antiviral prophylaxis in patients receiving immune checkpoint blocking agents requires further evaluation.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%